ANALISIS PENGGUNAAN DANA DESA DALAM MENINGKATKAN PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DI DESA KLETEK KECAMATAN MALAKA TENGAH KABUPATEN MALAKA - Marselina Clemens; R. Setyo Budi Suharto; Yunelci M. Seliamang (JAKA - Jurnal Jurusan Akuntasi, 2019)
This study aims to analyze the use of village funds in Kletek Village, Central Malaka District, Malacca Regency, assessed from the aspect of using village funds for development and community empowerment in 2016-2018.This research is a kind of descriptive research. The data used in this study are primary data and secondary data. Data collection techniques are done by interview, observation and documentation using qualitative methods.The results of this study indicate that the use of village funds in Kletek Village, Central Malaka Sub-district, Malacca Regency is not in accordance with the PDTT Permendes No. 19 of 2017. The use of village funds for the development sector carried out in Kletek Village is only focused on one development activity, namely procurement, / development / maintenance of basic infrastructure facilities to meet the needs that include the residential environment (drainage) and transportation (roads and bridges / deckers). Whereas in the field of community empowerment, there are activities to increase village capacity such as the provision of TTG in agriculture and savings and loan activities managed by Bumdes as well as an increase in weaving services. However, in its implementation the Village Government lacked transparency for the community, causing a slight dissatisfaction with the community towards the results of the activities / programs carried out.